Late toxicity in the brain after radiotherapy for sinonasal cancer: Neurocognitive functioning, MRI of the brain and quality of life. (November 2020) - Sharma, M.B.; Jensen, K.; Amidi, A.; Eskildsen, S.F.; Johansen, J.; Grau, C.
Highlights: Compared with matched normative data, impaired cognitive function was substantial. Several correlations between radiation dose and cognitive impairment were present. Radiation-induced white matter hyperintensities were present in 2/27 participants. One participant displayed radiation-induced necrosis in the temporal lobe. The domains affecting quality of life the most were fatigue and quality of sleep. Abstract: Purpose: The aim of the study was to evaluate neurocognitive late effects, structural alterations and associations between cognitive impairment and radiation doses as well as cerebral tissue damage after radiotherapy for sinonasal cancer. Furthermore, the aim was to report quality of life (QoL) and self-reported cognitive capacity. Materials and methods: Recurrence-free patients previously treated with intensity-modulated radiotherapy with a curative intent were eligible for the study. Study examinations comprised comprehensive neurocognitive testing, MRI of the brain, and self-reported outcomes. Results: A total of 27 patients were included. Median age was 67 years (range 47–83). The majority of test outcomes were below normative values in any degree, and 37% of the participants had clinically significant neurocognitive impairment when compared with normative data. Correlations between absorbed doses to specific substructures of the brain and neurocognitive outcomes were present for Wechsler's Adult Intelligence Scale-digit span and Controlled Oral Word Association Test-S. Structural MRI revealed macroscopic abnormalities in three patients; infarction (n = 1), diffuse white matter intensities (n = 2) and necrosis (n = 1). In the analysis of atrophy of cerebral tissue, no correlations were present with neither radiation dose to cerebral substructures nor neurocognitive impairment. The global QoL of the cohort was 75. The most affected outcomes were 'fatigue', 'insomnia', and 'drowsiness'. A total of 59% of participants reported significantly impaired quality of sleep. Self-reported cognitive function revealed that 'memory' was the most affected cognitive domain. For the domains of 'memory' and 'language', self-reported functioning was associated with objectively measured neurocognitive outcomes. Conclusion: Cerebral toxicity after radiotherapy for sinonasal cancer was substantial. Clinically significant cognitive impairment was present in more than one third of the participants, and several dose–response associations were present. Furthermore, the presence of macroscopic radiation sequelae indicated considerable impact of radiotherapy on brain tissue.